Batteries and Electrical Equipment

By adjusting the pore structure of lithium battery electrode plates and controlling electrolyte viscosity, the challenges of electrolyte flowback and lithium plating are addressed, resulting in improved cycle stability and capacity retention.

JP2025509528AActive Publication Date: 2025-04-11BYD CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2024554689
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-03-15
Filing Date
2023-03-15
Publication Date
2025-04-11
Estimated Expiration
2043-03-15

AI Technical Summary

Technical Problem

Lithium batteries face issues with electrolyte flowback during charge and discharge, leading to localized lithium plating and safety concerns, especially in large volume batteries.

Method used

Adjusting the pore diameters and pore size distribution of the positive and negative electrode plates, and controlling the viscosity of the electrolyte to enhance liquid retention capacity, ensuring timely electrolyte flowback and reducing lithium plating.

Benefits of technology

The solution improves cycle stability, retains high capacity, and extends battery cycle life by maintaining effective electrolyte interaction with the electrode plates.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025509528000001_ABST
    Figure 2025509528000001_ABST
Patent Text Reader

Abstract

A battery and an electrical device are provided. The battery's positive plate, negative plate, and electrolyte are [0010] Meet JPEG2025509528000010.jpg21168. Ce represents the electrolyte retention capacity of the positive and negative plates, A is a correction coefficient, a is the viscosity of the electrolyte at room temperature, R is the capacity of the battery, and B is the capacity of the battery. i and B. ii are the capillary index of the pore size of the positive electrode material layer and the capillary index of the pore size of the negative electrode material layer, respectively, i and ii are the average pore size value in the pore size range of the positive electrode material layer and the average pore size value in the pore size range of the negative electrode material layer, respectively, m and n are the maximum value in the pore size range of the positive electrode material layer and the maximum value in the pore size range of the negative electrode material layer, respectively, Pc i and Pa ii are the ratios of the pore volume of the positive electrode material layer when the pore size is i to the total pore volume, and the ratios of the pore volume of the negative electrode material layer when the pore size is ii to the total pore volume, respectively. The battery has good cycle stability and high capacity retention.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This disclosure claims priority to and the benefit of Chinese Patent Application No. 202210251599.0, entitled "BATTERY AND ELECTRICAL DEVICE," filed on March 15, 2022. The entire contents of the above-referenced application are hereby incorporated by reference.

[0002] The present disclosure relates to the technical field of lithium batteries, and in particular to batteries and electrical devices. [Background technology]

[0003] During charging and discharging of a lithium battery, the positive and negative plates undergo different degrees of volume change. Such volume change pushes out the electrolyte between the electrode plates of the battery core to flow back. However, the phenomenon that the electrolyte cannot flow back in a timely manner usually occurs in batteries with a large volume, especially in wound batteries and stacked batteries. If the electrolyte cannot flow back in a timely manner, some of the electrode plates in the battery core will not contact the electrolyte, resulting in localized lithium plating on the electrode plates during charging, even creating safety issues.

[0004] Currently, in the industry, this problem is usually solved by adjusting the composition of the electrolyte to increase the force between the electrolyte and the electrode plate. However, this method has high requirements for compatibility between the electrolyte and the type of electrode plate, and is not common or universal. Summary of the Invention [Problem to be solved by the invention]

[0005] In view of this, in the present disclosure, the pore size and respective pore size distribution of the positive and negative plates are adjusted, and the viscosity of the positive and negative plates and electrolyte are controlled, so as to ensure that the positive and negative plates have a strong electrolyte retention ability and reduce the occurrence of lithium plating during charging. As a result, the battery has good cycle stability, high capacity retention, and long battery cycle life. [Means for solving the problem]

[0006] According to a first aspect of the present disclosure, a battery is provided, the battery includes a positive electrode plate, a negative electrode plate, an electrolyte, and a separator located between the positive electrode plate and the negative electrode plate, the positive electrode plate includes a positive electrode current collector and a positive electrode material layer provided on the positive electrode current collector, the negative electrode plate includes a negative electrode current collector and a negative electrode material layer provided on the negative electrode current collector, and the positive electrode plate, the negative electrode plate, and the electrolyte satisfy the following formula:

number

[0007] In the formula, Ce is the electrolyte retention capacity of the positive and negative plates, Ce ranges from 1.0 g / Ah to 5.0 g / Ah, A is the correction factor, a is the viscosity of the electrolyte at room temperature, measured in mPa s, R is the capacity of the battery, measured in Ah, and B is the capacity of the battery. i is the capillary index of the pore size of the positive electrode material layer, and B ii is the capillary index of the pore size of the negative electrode material layer, and B i and B. ii is measured in meters, m is the maximum pore size of the pores in the positive electrode layer, i is the average pore size of the pores in the positive electrode layer, and Pc i is the ratio of the volume of the pores in the positive electrode material layer having a pore size i to the volume of the positive electrode material layer, n is the maximum pore size of the pores in the negative electrode material layer, ii is the average pore size of the pores in the negative electrode material layer, and Pa ii is the ratio of the volume of the pore in the negative electrode material layer having the pore size ii to the volume of the negative electrode material layer.

[0008] In some embodiments, R is in the range of 0.1 Ah to 300 Ah and A is in the range of 0.01 s to 100 s.

[0009] In some embodiments, R ranges from 10 Ah to 200 Ah.

[0010] In some embodiments, R ranges from 10 Ah to 100 Ah.

[0011] In some embodiments, the pore size distribution range of the positive electrode material layer is 20 nm to 20,000 nm, and the pore size distribution range of the negative electrode material layer is 20 nm to 20,000 nm.

[0012] In some embodiments, the value of i is 20000 nm, 18000 nm, 15000 nm, 12000 nm, 10000 nm, 7500 nm, 6500 nm, 5500 nm, 5000 nm, 3500 nm, 2500 nm, 1800 nm, 1200 nm, 750 nm, 500 nm, 320 nm, 200 nm, 140 nm, 90 nm, 65 nm, 50 nm, 40 nm, 30 nm, or 20 nm. m and the value of ii is 20000 nm, 18000 nm, 15000 nm, 12000 nm, 10000 nm, 7500 nm, 6500 nm, 5500 nm, 5000 nm, 3500 nm, 2500 nm, 1800 nm, 1200 nm, 750 nm, 500 nm, 320 nm, 200 nm, 140 nm, 90 nm, 65 nm, 50 nm, 40 nm, 30 nm, or 20 nm.

[0013] In some embodiments, the positive electrode layer has a porosity of 10% to 50%, and the negative electrode layer has a porosity of 10% to 70%.

[0014] In some embodiments, the minimum value of i and the minimum value of ii are both 50, and the value of m and the value of n are both 20000 nm.

[0015] In some embodiments, a is in the range of 0.5 mPa·s to 50 mPa·s.

[0016] In some embodiments, a is in the range of 0.5 mPa·s to 5 mPa·s.

[0017] In some embodiments, the electrolyte includes an organic solvent and a lithium salt, the lithium salt includes at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(oxalato)borate, lithium difluoro(oxalato)borate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium difluorophosphate, or lithium 4,5-dicyano-2-(trifluoromethyl)imidazole, and the organic solvent includes at least one of ethylene carbonate, diethyl carbonate, dimethyl carbonate, or ethyl methyl carbonate.

[0018] In some embodiments, the electrolyte includes a viscosity modifier, the viscosity modifier including at least one of a polyimide, a polyvinylidene difluoride, or a polyacrylic acid.

[0019] In some embodiments, the positive electrode material layer includes a positive electrode active material, a first conductive agent, and a first binder, and the negative electrode material layer includes a negative electrode active material, a second conductive agent, or a second binder.

[0020] According to a second aspect of the present disclosure, there is provided an electrical device comprising the battery provided in the first aspect of the present disclosure. [Brief description of the drawings]

[0021] [Figure 1] FIG. 1 is a schematic diagram of a battery structure according to one embodiment of the present disclosure. [Diagram 2] FIG. 1 is a schematic diagram of a structure of an electrical device according to one embodiment of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0022] Usually, when the volume of the active material in the positive and negative electrode layers expands during charging and discharging of the battery, the distance between the electrode plates decreases, and part of the electrolyte is pushed out. When the volume of the active material shrinks, the distance between the electrode plates increases, and the electrolyte flows back between the electrode plates. However, due to factors such as the flow characteristics of the electrolyte, the electrolyte cannot always flow back in a timely manner. As a result, part of the electrode plate in the battery core does not contact the electrolyte. As a result, localized lithium plating occurs, and the safety of using the battery is affected.

[0023] In order to solve the above technical problems, the embodiment of the present disclosure provides a battery. As shown in FIG. 1, the battery 10 includes a positive electrode plate 110, a negative electrode plate 120, an electrolyte 130, and a separator 140 between the positive electrode plate 110 and the negative electrode plate 120. The positive electrode plate 110 includes a positive electrode current collector 111 and a positive electrode material layer 112 disposed / disposed on the positive electrode current collector 111. The negative electrode plate 120 includes a negative electrode current collector 121 and a negative electrode material layer 122 disposed / disposed on the negative electrode current collector 121. The positive electrode plate, the negative electrode plate, and the electrolyte satisfy the following relationship:

number

[0024] In the formula, Ce represents the electrolyte retention capacity of the positive and negative plates, and the Ce value ranges from 1.0 g / Ah to 5.0 g / Ah; A is a correction coefficient; a is the viscosity of the electrolyte at room temperature, and the unit of viscosity is mPa s; R is the capacity of the battery, and the unit of capacity is Ah; B is the capacity of the battery, and the unit of capacity is Ah. i is the capillary index of the pore size of the positive electrode material layer, and B ii is the capillary index of the pore size of the negative electrode material layer, and B i and B. ii are both measured in meters (m), m is the maximum pore size in the range of pore sizes in the positive electrode layer, i is the average pore size in the range of pore sizes in the positive electrode layer, and Pc iis the ratio of the volume of the pore having the pore diameter i in the positive electrode material layer to the volume of the positive electrode material layer, n is the maximum pore diameter in the pore diameter range of the negative electrode material layer, ii is the average pore diameter in the pore diameter range of the negative electrode material layer, and Pa ii is the ratio of the volume of a pore in the negative electrode material layer having a pore size ii to the volume of the negative electrode material layer, where i and ii may be the same, and m and n may be the same.

[0025] In the present disclosure, the pore size i of the positive electrode material layer, the pore size ii of the negative electrode material layer, and the pore size distribution Pc i , and the pore size distribution Pa of the negative electrode material layer ii is configured so that the parameters and the viscosity a of the electrolyte can satisfy the above-mentioned relationship, so that the electrolyte retention ability of the positive and negative plates can be greatly improved (i.e., the interaction force between the electrode plates and the electrolyte is improved). When the viscosity of the electrolyte and the pore structure of the positive and negative plates satisfy the above-mentioned relationship, the permeability of the electrolyte in the electrode plates can be improved, and the electrolyte in the pores of the electrode plates cannot be easily pushed out of the electrode plates by the pressing force generated by the volume expansion of the active material. Therefore, the overflow of the electrolyte caused by the volume expansion of the electrode plates during the charging and discharging of the battery can be reduced. Even if a small amount of electrolyte flows out of the battery core, the electrolyte can flow back between the electrode plates in a timely manner due to the strong interaction force between the electrode plates and the electrolyte and the intermolecular force of the electrolyte. Therefore, the battery provided by the present disclosure can greatly reduce the problem of lithium plating on the surface of the electrode plate caused by a part of the electrode plate not contacting the electrolyte due to the electrolyte not flowing back in time, and further ensure that the battery has good cycle stability and safety and achieves high capacity.

[0026] m represents the maximum pore size in the range of pore sizes of the positive electrode material layer, i represents the average pore size in the range of pore sizes of the positive electrode material layer, and Pc iis the ratio of the volume of the pore in the positive electrode material layer when the pore size is i to the volume of the positive electrode material layer. n represents the maximum pore size in the range of pore sizes in the negative electrode material layer, ii represents the average pore size in the range of pore sizes in the negative electrode material layer, and Pa ii is the ratio of the volume of the pore in the negative electrode layer to the volume of the negative electrode layer when the pore size is ii. i and ii may be the same, and m and n may also be the same. B i and B ii is measured in meters. Ce values ​​range from 1.0g / Ah to 5.0g / Ah.

[0027] In the present disclosure, i is the average pore size value of the pore size in the pore size range of the positive electrode material layer, and ii is the average pore size value of the pore size in the pore size range of the negative electrode material layer. i and ii may be equal or may be positive integers. m is the maximum value in the pore size range of the positive electrode plate, and n is the maximum value in the pore size range of the negative electrode plate. Pci is the percentage of the pore size of the pores that corresponds to the average pore size value in the pore size range of the positive electrode plate, and Pa ii is the ratio of the pore size of the pores corresponding to the average pore size value in the pore size range of the negative plate. i, ii, Pc i , and Pa ii is related to the preparation conditions of the electrode plate, such as the pressed density of the active material, the particle engineering, and / or the various parameters in the coating and rolling techniques of the electrode plate. i and B. ii is related to the composition of the electrolyte and the start and end values ​​of the pore size range. Therefore, for the same pore size range, the value B i and the value of the negative electrode material layer B ii are the same. It should be noted that in this disclosure, the positive and negative plates may be collectively referred to as electrode plates. Pore size refers to the pores between particles in the positive or negative electrode material layers. Pore size range refers to the range of pore diameter values. Pore volume refers to the volume corresponding to a particular pore size.

[0028] In the above formula, the value a is the viscosity value of the electrolyte at room temperature measured by a viscometer. For example, the viscometer may be an Ubbelohde viscometer or a rotational rheometer. This is not limited in the present disclosure. It should be noted that viscosity in the present disclosure is the property of resisting deformation of adjacent fluid layers by a fluid or preventing relative movement.

[0029] Under conditions where the composition of the electrolyte and the composition of the electrode plates do not change, the value B i (or B ii ) is inversely proportional to the hole diameter value di: B i =k / di. Therefore, di-B of two or more groups i The value of is obtained through experiments, the value k is obtained by fitting the corresponding inverse proportional relationship, and the value B under different pore size values i (or B ii Specifically, three groups of capillaries with different diameters (2 μm, 10 μm, and 20 μm) are selected and inserted into the selected electrolyte, and the increase in height of the electrolyte in the capillary is measured. The height value is then used to obtain the corresponding pore size value B i k1, k2, and k3 are obtained, and the average value k is obtained. Then, the different values ​​di are substituted into the relational equation to obtain the corresponding value B i get.

[0030] In addition, the electrode plates i, ii, and Pc i , and Pa ii may also be obtained through testing. Specifically, the pore size and pore size distribution of the positive and negative plates are measured by using mercury intrusion porosimetry. The larger the range of pore sizes, and the smaller the pore size values, the higher the value B iSince the values ​​are closer in the lower pore size ranges, i and ii are the following values ​​in a specific embodiment, based on the porosity results of experimental testing: 20000nm, 18000nm, 15000nm, 12000nm, 10000nm, 7500nm, 6500nm, 5500nm, 5000nm, 3500nm, 2500nm, 1800nm, 1200nm, 750nm, 500nm, 320nm, 200nm, 140nm, 90nm, 65nm, 50nm, 40nm, 30nm, or 20nm. It should be noted that in mercury intrusion porosimetry, the pore size and pore size distribution of the pores are measured by applying external pressure to the mercury, allowing the mercury to overcome the surface tension and enter the pores. Porosity refers to the percentage of the volume of pores in a material relative to the total volume of the material in its natural state.

[0031] The inventors of the present disclosure have found through many experiments that the correction coefficient A is related to the material composition of the battery system, but A does not change with the change in the pore structure of the electrode plates. A larger value of A indicates a stronger force between the electrolyte and the positive and negative plates. The correction coefficient A needs to be obtained by fitting an initial simulation experiment. When the value A is fitted through an initial simulation experiment for the battery system (the battery is an entity), i, ii, B i , B ii , Pc i , and Pa ii are actually measured values, and Ce is also an actually measured value (denoted as Ce'). Ce' represents the actual electrolyte retention capacity of the electrode plate in the battery (specifically, a battery core with an opening is fabricated, an excess amount of electrolyte is injected into the battery core, the battery core is placed under a high vacuum level, and the content value of the electrolyte in the battery is measured after a certain period of time, which is the electrolyte retention capacity Ce' of the electrode plate). Then, the measured Ce' and values ​​i, ii, and B are i , B ii , Pc i , and Pa ii is substituted into the above equation to obtain the value A of the battery system.

[0032] The above-mentioned relationship provided in the present disclosure may be used to fabricate a battery having a predetermined electrolyte retention capacity. Specifically, after the value A of the battery system is obtained, the pore parameter Pc of the electrode plate is calculated. i and Pa ii is calculated based on the value Ce required by the battery being designed (i.e., the preset value), based on the above-mentioned relationship, and based on the actually measured value B i and B. ii It may be obtained through calculation with reference to. Therefore, in the process of making the positive and negative electrode plates, parameters such as the pressed density of the active material, particle engineering, and / or the coating technique and rolling technique of the electrode plate are adjusted to obtain the electrode plate and the battery that meet the above-mentioned pore structure. In addition, the set liquid-holding capacity of the battery for the electrolyte substantially matches the actual liquid-holding capacity of the battery for the electrolyte.

[0033] In addition, in existing battery systems, B i and B. ii are measured and the battery related parameters (A, i, ii, Pc i , and Pa ii ) are learned, and when these parameters are substituted into the aforementioned equation, the electrolyte retention capacity Ce of the electrode plate of the battery may be calculated. Then, an electrochemical performance test (e.g., a test on capacity retention, detection on the state of lithium plating, or a test on rate characteristics) is performed on the battery to establish a correspondence between the electrochemical performance of the battery and the value Ce. In this case, for another battery of this series, only the value Ce of the battery needs to be calculated in advance to estimate the cycle life of the battery. In some other cases, the value A of the battery and the value Ce' of the actual electrolyte retention capacity are obtained, and when these two values ​​are substituted into the aforementioned equation, the pore structure of the electrode plate may be obtained through calculation.

[0034] Specifically, the fitting of the correction coefficient A includes the following steps:

[0035] First, in the process of making the positive and negative plates of the battery, various parameters in the compression density of the active materials on the positive and negative electrodes, particle engineering, and / or the coating technique and rolling technique of the electrode plates are adjusted to make five groups of positive and negative plates with different pore structures. Then, the following tests are carried out.

[0036] (1) Value B i and value B ii Measure.

[0037] (2) Five groups of electrode plates i, ii, and Pc i , and Pa ii Measure the value.

[0038] (3) The positive electrode plate, separator, and negative electrode plate are stacked in order, and the positive electrode plate, separator, and negative electrode plate are assembled in a glove box to prepare five battery core samples, and the electrolyte retention capacity of the electrode plates in the battery cores is measured. It should be noted that in the above test, except for the pore size and pore size distribution of the positive electrode material layer and the negative electrode material layer, all other conditions are consistent. Specifically, the following steps are included:

[0039] A hole with a certain size is drilled in the housing of the battery core, and the mass of the battery core is weighed and recorded as M1. Then, an excess amount of electrolyte is injected under this condition, and evacuation is performed for 2 minutes under fixed vacuum conditions. Finally, the battery core is sealed, and the mass of the battery core is weighed and recorded as M2. The mass of the electrolyte in the test sample is recorded as Y, where Y=M2-M1. The value of Y / M is calculated. M is the sum of the mass of the positive electrode material layer in the positive plate and the mass of the negative electrode material layer in the negative plate, and the value of Y / M is the electrolyte retention capacity Ce' of the electrode plate.

[0040] (4) The values ​​Ce' of the five battery core samples are substituted into the above-mentioned equation, and the values ​​of each correction coefficient A under these experimental conditions are calculated to obtain the value A of the battery system. The values ​​A of the five groups are almost the same within the error range.

[0041] In this embodiment of the present disclosure, A is in the range of 0.01 s to 100 s. Controlling the value A to be within this range helps ensure the electrolyte retention ability of the electrode plate, thereby helping to provide a battery with good cycle stability, high capacity retention, and long cycle life.

[0042] In this embodiment of the present disclosure, R is in the range of 0.1 Ah to 300 Ah. In some specific embodiments, R is in the range of 10 Ah to 200 Ah. In some other specific embodiments, R is in the range of 10 Ah to 100 Ah. The above relationship defined in the present disclosure is universal for batteries with different capacities.

[0043] In an embodiment of the present disclosure, the porosity of the positive electrode material layer is in the range of 10% to 50%, and the porosity of the negative electrode material layer is in the range of 10% to 70%. The porosity of the positive electrode material layer and the negative electrode material layer may be the same or different. Controlling the porosity of the positive electrode plate and the negative electrode plate within the above range helps to improve the electrolyte retention capacity of the electrode plate and does not affect the performance of the positive electrode plate and the negative electrode plate.

[0044] In the embodiment of the present disclosure, the distribution range of the pore size of the positive electrode material layer and the distribution range of the pore size of the negative electrode material layer are 20 nm to 20000 nm. The actual distribution range of the pore size of the positive electrode material layer and the pore size of the negative electrode material layer may be the same or different. Controlling the pore size of the positive electrode material layer and the negative electrode material layer to be within the above-mentioned range is helpful in improving the electrolyte retention capacity of the electrode plate and in building a conductive network in the positive electrode plate and the negative electrode plate.

[0045] In an embodiment of the present disclosure, the values ​​of m and n are 20000 nm. Due to the large range of pore sizes in the porosity test results, and the smaller the pore size values, the value B iSince the difference in the pore size range is large, the values ​​are closer at the lower end of the pore size range. In some embodiments, the length of the pore size range may be 20 nm to 100 nm. For example, the length of the pore size range may be the following values: 20000 nm, 18000 nm, 15000 nm, 12000 nm, 10000 nm, 7500 nm, 6500 nm, 5500 nm, 5000 nm, 3500 nm, 2500 nm, 1800 nm, 1200 nm, 750 nm, 500 nm, 320 nm, 200 nm, 140 nm, 90 nm, 65 nm, 50 nm, 40 nm, 30 nm, or 20 nm.

[0046] In an embodiment of the present disclosure, a is in the range of 0.5 mPa·s to 50 mPa·s. For example, the value of a may be 0.5 mPa·s, 1.0 mPa·s, 2.0 mPa·s, 3.0 mPa·s, 4.0 mPa·s, 5.0 mPa·s, 6.0 mPa·s, 7.0 mPa·s, 8.0 mPa·s, 9.0 mPa·s, 10.0 mPa·s, 20 mPa·s, 30 mPa·s, 40 mPa·s, or 50 mPa·s. In some embodiments, a is in the range of 0.5 mPa·s to 5 mPa·s. For example, a may be 0.5 mPa·s, 1.5 mPa·s, 2.5 mPa·s, 3.5 mPa·s, 4.5 mPa·s, or 5.0 mPa·s. The appropriate viscosity of the electrolyte helps to improve the electrolyte retention capacity of the electrode plates, allows the electrolyte to wet the positive and negative electrode plates, and helps to maintain the internal resistance of the battery core within an appropriate range.

[0047] In an embodiment of the present disclosure, the electrolyte comprises an organic solvent and a lithium salt. The lithium salt comprises, but is not limited to, at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(oxalato)borate, lithium difluoro(oxalato)borate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium difluorophosphate, and lithium 4,5-dicyano-2-(trifluoromethyl)imidazole. The organic solvent comprises, but is not limited to, at least one of ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC).

[0048] In an embodiment of the present disclosure, the electrolyte further comprises a viscosity modifier. The viscosity modifier includes, but is not limited to, at least one of polyimide, polyvinylidene difluoride, and polyacrylic acid. The viscosity modifier is an inert organic liquid with high viscosity. The viscosity modifier can be added to adjust the viscosity of the electrolyte to a preset value to meet the design requirements of the battery without changing other components of the electrolyte.

[0049] In an embodiment of the present disclosure, the positive electrode material layer includes a positive electrode active material, a conductive agent (e.g., a first conductive agent), and a binder (e.g., a first binder). The negative electrode material layer includes a negative electrode active material, a conductive agent (e.g., a second conductive agent), and a binder (e.g., a second binder). The positive electrode active material, the negative electrode active material, the conductive agent, and the binder are all materials commonly used by those skilled in the art. For example, the positive electrode active material includes, but is not limited to, at least one of lithium iron phosphate, lithium manganese phosphate, lithium manganese iron phosphate, lithium vanadium phosphate, lithium cobalt phosphate, lithium cobalt oxide, lithium manganate, lithium nickel manganese oxide, lithium nickel manganese cobalt oxide (NCM), lithium nickel cobalt aluminum oxide (NCA), and lithium-rich manganese-based materials. For example, the negative electrode active material includes, but is not limited to, at least one of graphite, natural graphite, mesocarbon microbeads, and silicon carbon negative electrode materials.

[0050] The conductive agent includes, but is not limited to, at least one of carbon nanotubes (CNTs), carbon fibers (CFs), carbon black (such as acetylene black or ketjen black), furnace black, and graphene. The binder includes, for example, at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyvinyl alcohol (PVA), styrene butadiene rubber (SBR), polyacrylonitrile (PAN), polyimide (PI), poly(acrylic acid) (PAA), polyacrylate, polyolefin (such as polyethylene, polypropylene, polystyrene), carboxymethyl cellulose (CMC), and sodium alginate.

[0051] Correspondingly, the embodiment of the present disclosure further provides an electric device. As shown in FIG. 2, the electric device 1 includes a battery 10. The electric device may be a mobile terminal (such as a mobile phone, a notebook computer, or a tablet computer) or a motor vehicle. This is not limited in the present disclosure. The electric device includes a load connected to the battery. For example, the load may be various elements in a mobile terminal or a motor of a motor vehicle. The battery is configured to supply power to the load. Because a battery is used, the electric device has good battery life and safety performance.

[0052] The technical solutions of the present disclosure are described in detail by using several embodiments below.

[0053] EMBODIMENT 1 Preparation of electrolyte: EC, DMC, and DEC were mixed in a ratio of 4:3:3, and then a certain amount of LiPF6 was added so that the concentration of LiPF6 in the mixed solution was 1 mol / L. Then, a certain amount of viscosity modifier (polyimide) was added to obtain an electrolyte. The viscosity value a of the electrolyte at room temperature was tested by using a viscometer. The range length of the pore size was set to 50 nm, and the value B i was measured. B i =B ii .

[0054] Preparation of the positive electrode plate: 94% of the positive electrode active material (single crystal NCM811, D50 particle size was 3.87μm), 4% of the conductive agent (carbon black + CNT), and 2% of the binder (PVDF) were uniformly mixed with N-methyl-2-pyrrolidone (NMP) to prepare the positive electrode active material paste. The prepared positive electrode active material paste was coated on the aluminum foil of the positive electrode current collector by using a coating machine, and after drying, it was rolled and punched to obtain the positive electrode plate.

[0055] Preparation of negative electrode plate: To prepare the negative electrode active material paste, 96% of the negative electrode active material (graphite), 2% of the conductive agent (acetylene black), and 2% of the binder (PVDF) were mixed uniformly with NMP to obtain the negative electrode active material paste. The prepared negative electrode active material paste was coated on the copper foil of the negative electrode current collector, dried, and then rolled and punched to obtain the negative electrode plate.

[0056] Measurement of the pore structure of the electrode plates: values ​​i, ii, Pc of the positive and negative plates i , and Pa ii is measured,

number

[0057] The positive electrode plate, the separator, and the negative electrode plate were alternately stacked, and a dry battery core was fabricated by stacking. The capacity R value of the battery core was 9.2 Ah. The separator alternately isolates the positive electrode plate and the negative electrode plate. The dry battery core was placed in an exterior of an encapsulating aluminum laminated film, dried, and injected with an electrolyte. After formation, a battery of embodiment 1 was obtained and designated S1.

[0058] According to the battery manufacturing method provided in embodiment 1, the batteries of embodiments 2 to 14 were manufactured based on the ratios in Table 1, and the batteries of embodiments 2 to 14 were designated as S2 to S14, respectively. [Table 2]

[0059] Specifically, NCM811 is LiNi 0.8 Co 0.1 Mn 0.1O2. NCM622 is specifically LiNi 0.6 Co 0.2 Mn 0.2 O2. NCM523 is specifically LiNi 0.5 Co 0.2 Mn 0.3 It was O2.

[0060] In order to highlight the beneficial effects of the embodiments of the present disclosure, the following three comparative examples are provided. According to the battery manufacturing method provided in embodiment 1, the batteries of Comparative Examples 1 to 3 were manufactured based on the ratios in Table 2, and the batteries of Comparative Examples 1 to 3 were designated as DS1 to DS3, respectively. [Table 3]

[0061] Electrochemical performance tests were carried out on the batteries fabricated in the above embodiments and comparative examples, with the details as follows:

[0062] (1) Detection on the state of lithium plating: 0.5C / 0.5C cycle tests were conducted on the batteries at 25°C, with the voltage range of 2.5V~4.2V. The state of lithium plating on the negative electrode of the batteries after 500 cycles was recorded, and the results were summarized in Table 3.

[0063] (2) Cycle performance test: A 0.5C / 0.5C cycle test was conducted on the battery at 25° C., and the voltage range was 2.5 V to 4.2 V. The capacity retention of the battery after 500 cycles was recorded, and the results are summarized in Table 3.

[0064] (3) High-current performance test: A high-current charge / discharge test was performed on the battery at 25°C, the voltage range was 2.5V to 4.2V, and charging / discharging was performed using a high current of 5C / 5C. The capacity retention of the battery was recorded, and the results are summarized in Table 3. [Table 4]

[0065] With reference to the battery parameters in Tables 1 and 2, and the battery test results in Table 3, it can be seen that the batteries satisfying the relationship defined in the present disclosure had excellent electrochemical performance. Specifically, the batteries S1 to S14 of the embodiment all had good capacity retention. Comparing the battery S1 with the battery DS1, under the same experimental conditions, an electrolyte with an excessively low viscosity was used for DS1, and the value Ce of DS1 was excessively small. As a result, the lithium plating state of the battery was serious, and the capacity of the battery was rapidly deteriorated. Comparing the battery S1 with the battery DS2, the value Ce of the battery DS2 exceeded the upper limit defined in the present disclosure, and the internal resistance of the battery was large, resulting in a very low capacity retention of the battery at a high rate of 5C current. Comparing the battery S1 with the battery DS3 under the same experimental conditions, the excessively small porosity of the electrode plate of DS3 led to a small value Ce, resulting in serious lithium plating of the battery and rapid deterioration of the capacity of the battery.

[0066] The foregoing are exemplary embodiments of the present application. It should be noted that those skilled in the art may further make some improvements and modifications without departing from the principle of the present disclosure, and the improvements and modifications shall fall within the protection scope of the present disclosure. [Explanation of symbols]

[0067] 1. Electrical Equipment 10 batteries 110 Positive plate 111 Positive electrode current collector 112 Positive electrode material layer 120 Negative plate 121 Negative electrode current collector 122 Negative electrode material layer 130 Electrolyte 140 Separator 150 Battery Case

Claims

1. A battery (10) comprising a positive electrode plate (110), a negative electrode plate (120), an electrolyte (130), and a separator (140) between the positive electrode plate and the negative electrode plate, the positive electrode plate comprising a positive electrode current collector (111) and a positive electrode material layer (112) disposed on the positive electrode current collector, the negative electrode plate comprising a negative electrode current collector (121) and a negative electrode material layer (122) disposed on the negative electrode current collector, the positive electrode plate, the negative electrode plate, and the electrolyte satisfy the following relationship: [0010] Fulfilling where Ce is the electrolyte retention capacity of the positive and negative plates, Ce having a value ranging from 1.0 g / Ah to 5.0 g / Ah; A is a correction factor, a is the viscosity of the electrolyte at room temperature, measured in mPa·s; R is the capacity of the battery, measured in Ah; B is the capacity of the battery, measured in Ah; i is the capillary index of the pore size of the positive electrode material layer, and B ii is the capillary index of the pore size of the negative electrode material layer, and B i and B ii is measured in meters, m is the maximum pore size of the pores in the positive electrode layer, i is the average pore size of the pores in the positive electrode layer, and Pc i is the ratio of the volume of a pore having a pore diameter i in the positive electrode material layer to the volume of the positive electrode material layer, n is the maximum pore diameter of the pores in the negative electrode material layer, ii is the average pore diameter of the pores in the negative electrode material layer, and Pa ii is the ratio of the volume of the pores in the negative electrode material layer having a pore size ii to the volume of the negative electrode material layer; Battery (10).

2. 2. The battery of claim 1, wherein R is in the range of 0.1 Ah to 300 Ah and A is in the range of 0.01 s to 100 s.

3. 3. The battery of claim 1, wherein R is in the range of 10 Ah to 100 Ah.

4. The battery according to any one of claims 1 to 3, wherein the pore size distribution range of the positive electrode material layer is 20 nm to 20,000 nm, and the pore size distribution range of the negative electrode material layer is 20 nm to 20,000 nm.

5. 5. The battery according to claim 1, wherein the positive electrode layer has a porosity of 10% to 50%, and the negative electrode layer has a porosity of 10% to 70%.

6. 6. The battery of claim 1, wherein the minimum value of i and the minimum value of ii are 50, and the values ​​of m and n are 20,000 nm.

7. The value of i is 20000 nm, 18000 nm, 15000 nm, 12000 nm, 10000 nm, 7500 nm, 6500 nm, 5500 nm, 5000 nm, 3500 nm, 2500 nm, 1800 nm, 1200 nm, 750 nm, 500 nm, 320 nm, 200 nm, 140 nm, 90 nm, 65 nm, 50 nm, 40 nm, 30 nm, or 20 nm; and the value of ii is 20000 7. The battery of claim 1 , wherein the optical fiber has a wavelength of 1000 nm, 18000 nm, 15000 nm, 12000 nm, 10000 nm, 7500 nm, 6500 nm, 5500 nm, 5000 nm, 3500 nm, 2500 nm, 1800 nm, 1200 nm, 750 nm, 500 nm, 320 nm, 200 nm, 140 nm, 90 nm, 65 nm, 50 nm, 40 nm, 30 nm, or 20 nm.

8. The battery according to any one of claims 1 to 7, wherein a is in the range of 0.5 mPa·s to 50 mPa·s.

9. 9. The battery of any one of claims 1 to 8, wherein the electrolyte comprises an organic solvent and a lithium salt, the lithium salt comprises at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(oxalato)borate, lithium difluoro(oxalato)borate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium difluorophosphate, or lithium 4,5-dicyano-2-(trifluoromethyl)imidazole, and the organic solvent comprises at least one of ethylene carbonate, diethyl carbonate, dimethyl carbonate, or ethyl methyl carbonate.

10. 10. The battery of claim 1, wherein the electrolyte comprises a viscosity modifier, the viscosity modifier comprising at least one of a polyimide, a polyvinylidene fluoride, and a polyacrylic acid.

11. 11. The battery of claim 1, wherein the positive electrode layer comprises a positive electrode active material, a first conductive agent, and a first binder, and the negative electrode layer comprises a negative electrode active material, a second conductive agent, and a second binder.

12. An electrical device (1) comprising a battery (10) according to any one of claims 1 to 11.

Citation Information

Patent Citations

  • Lithium ion battery and preparation method thereof

    CN111403801A

  • Graphite particle for nonaqueous secondary battery, negative electrode for nonaqueous secondary battery using the same, and nonaqueous secondary battery

    JP2014067680A

  • Negative electrode of non-aqueous electrolyte secondary cell and non-aqueous electrolyte secondary cell

    WO2013047016A1